Investigasi Loyalitas Penumpang Kereta Api Pengguna KAI Acces - Triani, Ririn Agus; Yenita, Yenita (Universitas Bina Sarana Informatika, 2023)
Standar layanan pelanggan perlu ditingkatkan agar untuk mendorong penggunaan jasa transportasi darat, khususnya kereta api. Maksud penelitian ini yaitu memberi informasi tentang faktor yang memengaruhi loyalitas pelanggan kereta api melalui kegiatan investigasi dalam upaya meningkatkan hal tersebut. Analisis memanfaatkan PLS-SEM dalam penelitian, ini dimaksudkan untuk dimanfaatkan dalam menganalisis data yang menyimpang dari asumsi normalitas dan signifikansi statistik. Sampel untuk kegiatan penelitian terdiri dari penumpang kereta api yang menggunakan KAI Acces dalam pemesanan tiket sebanyak 100 responden. Penelitian yang telah dilaksanakan mengungkapkan dampak positif positif dari service quality dan perceived value kepada customer loyalty melalui customer satisfaction dari hasil investigasi. Untuk pengujian perceived value serta service quality kepada customer satisfaction, semuanya juga mempunyai dampak yang positif. Sedangkan untuk pengujian service quality serta perceived value kepada customer loyalty secara langsung tanpa mediasi customer satisfaction, untuk service quality tidak mempunyai dampak yang positif kepada customer loyalty, sedangkan perceived value memiliki dampak positif. Dapat diambil kesimpulan bahwa peran customer satisfaction sebagai variabel intervening mempunyai efek partial mediation pada pengujian variabel perceived value dan full mediation pada pengujian service quality.The use of land transportation is believed to be a profitable business, one cannot separate ts position as one of the most crucial participants in both marine and air transportation alternatives, especially in Indonesia. To increase the use of rail and other ground transportation options, customer service standards must be raised. Through investigative activities, this study aims to increase railroad customer loyalty by providing information on their level of loyalty. The following are some of the research hypotheses: H1) The findings demonstrate that client quality of service has an impact on satisfaction; H2) According to the investigation's findings, client satisfaction is influenced by perceived value; H3) According to the study's findings, customer loyalty is influenced by service quality; H4) The investigation's findings indicate that perceived value has an impact on customer loyalty; H5) According to the investigation's conclusions, Client loyalty is influenced by customer happiness and the the caliber of the services rendered. In addition, service quality, customer satisfaction, perceived value, and customer loyalty are the four categories of variables investigated. Issues are addressed combining structural equation modeling with partial least squares (PLS-SEM), we conducted this study that deviate from the assumptions of adequacy and normality of the sample. Train riders who book tickets through KAI Access make up the research activity's sample. Based on research findings, customer loyalty and satisfaction are significantly influenced favorably by service quality and perceived value factors.